2021
DOI: 10.1002/jbt.22839
|View full text |Cite
|
Sign up to set email alerts
|

Rosmarinic acid relieves cisplatin‐induced ovary toxicity in female mice via suppression of oxidative stress and inflammation

Abstract: Rosmarinic acid having potential anti-inflammatory and free radical scavenging activity. We examined the chemotherapeutic effect of rosmarinic against cisplatin (CIS)-induced ovarian toxicity via modulation of oxidative stress and inflammation.Swiss BALB mice used in experimental protocol and mice were divided into different groups. Intraperitoneal injection of CIS (7 mg/kg) was used for ovarian cancer induction. The rats were received rosmarinic acid (2.5, 5, and 10 mg/kg, body weight) treatment for 22 weeks.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…In addition, RA induced G1/S cell cycle arrest and apoptosis in the pancreatic ductal adenocarcinoma cells by regulating apoptotic genes' expression. In Swiss BALB mice, RA exposure displayed protective effects in cisplatin-induced ovarian toxicity through modulation of anti-oxidant and anti-inflammatory parameters (Gui et al 2021 ). RA exposure ameliorated doxorubicin-mediated cardiotoxicity in both in vitro and in vivo models and, therefore, also be a promising drug for combating anti-cancer drug-mediated toxicity (Rahbardar et al 2021 ).…”
Section: Clinical Implications Of Ramentioning
confidence: 99%
“…In addition, RA induced G1/S cell cycle arrest and apoptosis in the pancreatic ductal adenocarcinoma cells by regulating apoptotic genes' expression. In Swiss BALB mice, RA exposure displayed protective effects in cisplatin-induced ovarian toxicity through modulation of anti-oxidant and anti-inflammatory parameters (Gui et al 2021 ). RA exposure ameliorated doxorubicin-mediated cardiotoxicity in both in vitro and in vivo models and, therefore, also be a promising drug for combating anti-cancer drug-mediated toxicity (Rahbardar et al 2021 ).…”
Section: Clinical Implications Of Ramentioning
confidence: 99%
“…Therefore, the daily consumption of vitamin-rich foods as non-enzymatic antioxidant supplements, or superoxide dismutase (SOD), catalase (CAT), and other health products as the supplements of antioxidant enzymes can effectively remove free radicals. Studies have shown that phenolic antioxidant RA had the function of scavenging free radicals, including ROS and H 2 O 2 , and enhanced antioxidant enzymes and non-enzymic antioxidants [ 70 , 71 ]. The antioxidant effect of RA is mainly related to preventing tumorigenesis and chemosensitization.…”
Section: Biological Processes and Mechanism Of Action Of Ra In Tumor ...mentioning
confidence: 99%
“…In addition, the antioxidant activity of RA can improve the toxicity of anti-tumor therapy. The antioxidation properties of RA protected ovaries without attenuating the anti-tumor effect of cisplatin [ 71 ]. RA improved the hepatorenal toxicity induced by methotrexate and cardiotoxicity induced by DOX based on antioxidant activity [ 82 , 83 , 84 ].…”
Section: Biological Processes and Mechanism Of Action Of Ra In Tumor ...mentioning
confidence: 99%
“…The extensive literature has shown the therapeutic potential of RA as antibacterial [25], antiviral [26], anti-inflammatory [27], anti-cancer [28], immunological modulation [29], health-enhancing [22], and containing antioxidant properties [30]. Among these activities, a significant number of reports have highlighted the anticancer activity of RA [31][32][33][34][35]. Hence, it is important to investigate the role of RA as an anticancer lead which might further lead to the discovery of a new cytotoxic drug.…”
Section: Introductionmentioning
confidence: 99%